Causation in criminal law : a research companion - Reed, Alan; Bohlander, Michael, 1962-; Simpson, Bethany; Adams, Verity (Substantive issues in criminal law (Abingdon, England), 2026)
"This collection presents a leading contribution in the substantive arena relating to Causation in Criminal Law. Extant law reveals significant problems in adoption of consistent approaches to doctrinal and theoretical underpinnings of legal causation and culpability thresholds. This has been exemplified by a plethora of recent jurisprudential authorities revealing varying degrees of confusion and vacillation. A variety of Law Commission proposals, although emboldening the debate, have yet to be adopted in any logical template. The volume addresses three specific elements within this arena, embracing an overarching synergy between them. This edifice engages in an examination of UK provisions, with specialist contributions on domestic law, and in contrasting these provisions against alternative domestic jurisdictions as well as comparative contributions addressing a particularised research grid for content. The comparative chapters provide a wider background of how other legal systems treat a variety of specialised issues relating to causation in the context of the criminal law. With contributions from leading experts in the field, the book will be an invaluable resource for researchers, academics, and practitioners working in Comparative Criminal Law and related areas"--